Adobe Illustrator CS3 - Ferguson, Dwayne; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
This video will introduce users to the tools and operations available in illustrator CS3. User will then practice what they have learned by creating two exciting projects. Work files are included
Title from container
Trainig CD
Contains 126 movies with total time 7.5 hours
See record from bib id 3424179 for payment details
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Adobe Illustrator; Computer graphics